(untitled) (Journal of Guidance and Counselling Studies, 2022)
This study investigated effects of imago therapy and emotional focused therapy on marital adjustment of couples among primary school teachers in Abia State. The study adopted a Quasi-experimental design of pretest, posttest and control group using 2x2 factorial matrix. A total of 30 married teachers that were sampled from a population of 483 primary school teachers identified to have marital challenges in the state were used for the study. These comprised 10 married teachers each for imago therapy, emotional focused therapy and control groups respectively. The study equally adopted multi-staged sampling. The instruments used for data collection were Marital Conflict Identification Questionnaire (MCIQ) containing22-items and 20-item Marital Adjustment Questionnaire (MAQ). The instruments were validated by three research experts made up of one from Guidance and Counselling, Educational Psychology and Educational Measurement and Evaluation all in College of Education, Michael Okpara University of Agriculture Umudike, Abia State. Pearson Product Moment Correlation coefficients as well as Cronbach alpha statistic were used to test for the stability and internal consistency of the instruments which yielded indices of 0.78 and 0.83 respectively. Data were collected in three phases of pre-treatment phase, post-treatment phase and the follow-up phase. Data collected were analyzed using mean and standard deviation to answer the research questions and Analysis of Covariance (ANCOVA) to test the null hypotheses at 0.05 level of significance. The results showed among others that imago therapy and emotional focused therapy combined significantly improve marital harmony among the maladjusted couples in Abia state. It enhances factors such as couples’ expectations of each other, parenting styles, financial issues, friends, sexual relations, and relationships with relatives. Based on the findings, discussion, implication and recommendation were made. One of the recommendations was that teachers who have some identified couples with marital maladjustment could effectively reduce it using imago therapy and emotional focused therapy.